2019
DOI: 10.1111/risa.13440
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effects of Recall Bias and Selection Bias on the Epidemiological Evidence for the Carcinogenicity of Glyphosate

Abstract: Glyphosate is a widely used herbicide worldwide. The International Agency for Research on Cancer in 2015 declared that glyphosate is probably carcinogenic to humans, noting a positive association for non-Hodgkin lymphoma (NHL). The principal human data on glyphosate and NHL come from five case-control studies and two cohort studies. The case-control studies are at risk of recall bias resulting from information on exposure to pesticides being collected from cases and controls based on their memories. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The International Agency of the World Health Organization recently classified glyphosate as "possibly carcinogenic to humans" [73]. Although some researchers believed that glyphosate was not linked to carcinogenicity, epidemiological evidence supports a strong temporal correlation between the use of glyphosate on crops and a multitude of cancers, including breast cancer, pancreatic cancer, kidney cancer, thyroid cancer, and liver cancer [74].…”
Section: Discussionmentioning
confidence: 99%
“…The International Agency of the World Health Organization recently classified glyphosate as "possibly carcinogenic to humans" [73]. Although some researchers believed that glyphosate was not linked to carcinogenicity, epidemiological evidence supports a strong temporal correlation between the use of glyphosate on crops and a multitude of cancers, including breast cancer, pancreatic cancer, kidney cancer, thyroid cancer, and liver cancer [74].…”
Section: Discussionmentioning
confidence: 99%
“…This study presented some limitations. Firstly, the SEER database is a retrospective dataset with limitations inherent to retrospective research, for example retrospective analysis is prone to selection and recall bias (35). Moreover, the data from the SEER database were collected by different cancer centers and, depending on the statistician, there may be selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse health effects associated with glyphosate, the most widely used herbicide worldwide, is the focus of intense regulatory debate. With studies opposed, some of them confirmed the effects (Zhang et al., 2019 ) and other studies in other way (Andreotti et al., 2018 ; Crump, 2020 ), glyphosate was classified as “probably carcinogenic” for humans in March 2015 by the International Agency for Research on Cancer (IARC, 2015 ). Actually, many countries, regions, and municipalities have banned or are strictly regulating its use ( http://sustainablepulse.com ).…”
Section: Introductionmentioning
confidence: 87%